Wayang Santri 'Lupit Dan Slentheng': Aset Budaya Sarana Dakwah Di Kabupaten Tegal - Hamidah, Nur; Naam, Moh. Fakhrihun; Sugiarto, Eko (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This research aims to describe and analyze the model of Islamic da'wah based on local wisdom contained in wayang santri performances. The Islamic da'wah model is a pattern or approach used to broadcast Islamic values. Wayang santri is a concept for wayang performances that are specifically used for preaching purposes. This research uses a qualitative research method with a descriptive approach that describes a model of Islamic da'wah with sources from the wayang santri artistic apparatus including puppeteers, sinden and wayang santri music players. This research produces several important points regarding the Islamic preaching model based on local wisdom in the art of wayang santri, namely regarding the origins and history of the development of wayang santri, the beauty contained in wayang santri performances, and the Islamic values ​​contained in wayang santri performances.